Entrepreneurial Potential: An Exploratory Study Of A Community In Johor - Amir, Aris; Ahmad Rozelan, Yunus; Azizah, Shaaban; Janatul Islah, Mohammad (2012)
Two frequently cited personal traits associated with entrepreneurial potential are internal locus of control and innovativeness. This paper hypothesizes that internal locus of control and innovativeness is sufficient to explain entrepreneurial potential. This hypothesis was tested on a set of 124 responses to a survey did to a community in Johor. Eighteen items in the survey instrument were used to construct scales for innovativeness and locus of control. Items for the innovativeness scale were adapted from the Jackson Personality Inventory while items used for the locus of control scale were adapted from Rotter’s I-E scale. The results found an increased likelihood of an internal locus of control and innovativeness that support entrepreneurial orientation. To be motivated to act, potential entrepreneurs must perceive themselves as capable and psychologically equipped to face the challenges. This work has been supported by Universiti Teknikal Malaysia Melaka (UTeM) and Ministry of Higher Education Malaysia. Keywords: Entrepreneurial Potential, Locus of Control, Innovativeness,Community